Numerical Study for the Evaluation of the Effectiveness and Benefits of Using Photovoltaic-Thermal (PV/T) System for Hot Water and Electricity Production under a Tropical African Climate: Case of Comoros - Fahad Maoulida; Rabah Djedjig; Mohamed Aboudou Kassim; Mohammed El Ganaoui (Energies, 2022)
Several rural regions located in Africa are experiencing recurrent and even permanent problems in terms of energy production, supply, and distribution to citizens. This study was conducted to investigate the relevance of the use of a new solar technology that is gradually responding in Europe and in industrialized countries. It is about the use of hybrid photovoltaic thermal (PV/T) solar panels that co-produce electricity and hot water for local use. Furthermore, in Africa, local use of solar energy can provide a share in the energy mix. This work is motivated by the lack of studies on these hybrid solar panels in tropical climates. Hence, the paper examines the potential for integration of these systems in small households. A complete PV/T system consisting of solar panels, pump, storage tank, batteries, and controllers was tested and calibrated by using the TRNSYS simulation tool. A comparative study could thus be carried out for the performance of PV/T in a tropical climate (case of the city of Koua in the Comoros) to its performance in Mediterranean and continental climates (Marseille in the south and Longwy in the northeast of France). The results quantify the performance of the PV/T in the three climates and show that the performance in the town of Koua is 44% to 54% higher than in European climates. It can be concluded from this study that the Comorian market and more generally the sub-Saharan market for PVT systems has a good potential for development.